GHOSTING DALAM HUBUNGAN ROMANTIS: TINJAUAN PSIKOLOGIS DAN SOSIOLOGIS DALAM HUBUNGAN MODERN - Hari Ramdani; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (Yayasan Literasi Sains Indonesia, 2025)
This study discusses the phenomenon of ghosting in romantic relationships by utilizing psychological and sociological approaches in the context of the digital era. The methodology used is a qualitative approach through literature study and in-depth interviews with six participants, consisting of three perpetrators and three victims of ghosting. The main objective of this study is to explore the causes, impacts, and preventive measures against ghosting. The findings show that ghosting behavior is influenced by psychological aspects, such as avoidant attachment style and moral disengagement, as well as sociological aspects such as individualism culture and easy access to technology. The impacts felt by victims include decreased self-esteem, anxiety, and difficulty in building trust. Meanwhile, perpetrators can experience feelings of guilt or relief, depending on the motivation behind their actions. Efforts to reduce ghosting include increasing honest and open communication, education about psychological impacts, and wise use of technology. The conclusion of this study emphasizes the importance of implementing a multidisciplinary approach in understanding ghosting in order to encourage the formation of healthier romantic relationships in the digital era.